PENGEMBANGAN KOMIK IPA BERBASIS KARAKTER PEDULI LINGKUNGAN PADA MATERI STRUKTUR DAN FUNGSI BAGIAN TUMBUHAN (Uji Coba Siswa Kelas IV SD Muhammadiyah Kleco) - Arum Syafrilia Trisnaningsih; Ika Maryani (Universitas Ahmad Dahlan, 2018)
This study aims to: 1) know the development steps of IPA based on environmental character concerns on the structure and function of the pupil part IV grade elementary school, 2) to know the feasibility of science-based character-based IPA character on the material structure and function of plant part IV fourth grade. This research is a research development (Research and Development) using a model used by Robert Maribe Brance is the development of ADDIE. The subject of this research is the fourth grader of SD Muhammadiyah Kleco Kotagede Yogyakarta. Data collection techniques on product trials using teacher and student assessment questionnaires.The results showed that the assessment of media experts get the value of 83.3 with the category of